2020
DOI: 10.1016/j.autcon.2020.103285
|View full text |Cite
|
Sign up to set email alerts
|

Towards the adoption of automated regulatory compliance checking in the built environment

Abstract: Automated compliance checking brings advantages to the built environment but, currently, there has been no meaningful adoption, despite the increasing maturity of asset information models. This paper addresses this by ascertaining the blockers/obstacles to adoption and develops a road-map to overcome them. This work has been conducted in the UK and a road-map has been produced to drive forward adoption. More specifically this paper has; assessed the current state of the art in the field and engaged with indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…Studies show that ARC systems, designed based on user requirements, not only succeed in terms of rule checking but also result in additional benefits originated from cultural shifts and changes in practice. For instance, if ARC is designed and implemented successfully, it might result in wider adoption of BIM, which then improves many other aspects of design and construction [10]. Furthermore, users working with well-designed ARC systems are more likely to gain a better tacit understanding of the codes (rules) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that ARC systems, designed based on user requirements, not only succeed in terms of rule checking but also result in additional benefits originated from cultural shifts and changes in practice. For instance, if ARC is designed and implemented successfully, it might result in wider adoption of BIM, which then improves many other aspects of design and construction [10]. Furthermore, users working with well-designed ARC systems are more likely to gain a better tacit understanding of the codes (rules) [11].…”
Section: Introductionmentioning
confidence: 99%
“…BMC has been a focus of research and development for years, but its practical use throughout the years been reported as limited (Dimyadi and Amor 2013, Refvik et al 2014, Beach et al 2020. While, there exist many BMC solutions a recent study by Beach et al (2020) indicated that "there has been no meaningful adoption, despite the increasing maturity". The adoption of BMC is considered by some researchers slow and problematic (Refvik et al 2014, Beach et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…While, there exist many BMC solutions a recent study by Beach et al (2020) indicated that "there has been no meaningful adoption, despite the increasing maturity". The adoption of BMC is considered by some researchers slow and problematic (Refvik et al 2014, Beach et al 2020. Beach et al 2020 found that some of the reasons to be related to lack of shared open standards for regulation clauses, not tools to offer a complete ability of precheck for compliance prior to formal submissions, cultural resistance.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a roadmap for automated compliance checking adoption, Beach et al (Beach, et al, 2020) conducted a detailed inventory of applicable industrial and academic developments. With the aid of industry partners, the authors identified and analysed the tools currently allowing model compliance checking.…”
Section: Introductionmentioning
confidence: 99%
“…Several other academic research platforms were analysed using these same criteria. Then, by conducting a survey with industry partners, the authors identified a list of obstacles to the adoption of automated compliance checking that led them to propose a roadmap that considered, concurrently, the political, commercial, and technological factors in the future development of automated compliance checking (Beach, et al, 2020). Although industrial partners were in favour of adopting automated compliance checking, they insisted on the necessity for designating a qualified human to supervise the whole process.…”
Section: Introductionmentioning
confidence: 99%